Influence of delay between dental bleaching with 35% hydrogen peroxide and orthodontic brackets on the bond strength at the enamel/adhesive interface - de Almeida, Antônio-Augusto-Lima (J Clin Exp Dent, 2019)
BACKGROUND: The aim of this study was to evaluate the influence of waiting time between the bleaching with 35% hydrogen peroxide and orthodontic brackets bonding on shear bond strength (SBS) in enamel. MATERIAL AND METHODS: Eighty bovine teeth were randomly divided into four groups (G): G1(negative control) and G2, G3 and G4 (experimental groups). The experimental groups were submitted to bleaching. Prior to orthodontic brackets bonding to enamel the procedure was adopted different waiting times, as follows: G2 (1 day); G3 (7 days) and G4 (14 days). It was performed enamel etching (30s), washing water (30s), application of adhesive system followed by photoactivation (20s). A thin layer of composite resin was placed between the adhesive and the brackets. The applied pressure was measured by tensiometer (300N/40s). The composite resin was light-cured (40s). After 24 hours the shear test was held (0.5mm/min). To compare the SBS it was used ANOVA one-way followed by Tukey test (α = 0.05). The Adhesive Remaining Index (ARI) was analyzed using the Kruskal-Wallis test. RESULTS: The SBS values were significantly lower in G2 (15.51 MPa) and G3 (17.77 MPa) compared to G1 (30.14 MPa) and G4 (28.50 MPa) (p<0.05). The ARI revealed significant difference between the G3 and the other groups (p<0.05). CONCLUSIONS: It was concluded that the bond strength in enamel in the interfaces/adhesive system/composite resin/orthodontic brackets was more effective 14 days after the bleaching with 35% hydrogen peroxide. Key words:Dental materials, teeth bleaching, orthodontic brackets.